Implementation of supply chain management using the ERP system at XYZ Company Indonesia - Yulia Segarwati; Nurhayati Nurhayati; Trisa Nurkania; Yuyun Yuniarti; Maun Jamaludin (LifeSciFi, 2022)
Supply Chain Management (SCM) is a network of companies working to create and deliver a product to the end user. These companies include suppliers, factories, distributors, shops or retail, as well as supporting companies such as logistics services. The company is integrated with an ERP or enterprise resource planning system that combines each department into one database to save time in its use. In this study, researchers implemented supply chain management and this ERP system at XYZ Company Indonesia. A company engaged in the marketing and distributing various goods for consumption, including toiletries, body care, cosmetics, and cooking spices, which of course, gives an advantage if it can implement this supply chain management and ERP system.